2006
DOI: 10.1056/nejmc052939
|View full text |Cite
|
Sign up to set email alerts
|

Attendance at Supervised Injecting Facilities and Use of Detoxification Services

Abstract: T h e ne w e ngl a nd jou r na l o f m e dic i ne n engl j med 354;23 www.nejm.org june 8, 2006 2512 stances after a disaster, the heavy workload, panic, and incomplete patient records. 1 However, despite these drawbacks, crush injuries after the Marmara earthquake, in Turkey, which formed the main basis for our article, were documented in as much detail as possible regarding the fate of the injured persons, their profile, and any nephrologic problems, thanks to the high rate of response to questionnaires t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(102 citation statements)
references
References 4 publications
5
97
0
Order By: Relevance
“…21 Because an addiction counsellor is on site at the facility and other facility staff refer IDUs to addiction services, an evaluation was undertaken to examine factors associated with more rapid entry into a detoxification program among facility users. 33 Definition of this end point was based on linkage to a database maintained by Vancouver's 3 detoxification facilities, which offer medically monitored residential withdrawal services with on-site nursing and medical care. The study period considered each participant's recruitment date up until Mar.…”
Section: Referral For Addiction Treatment and Other Carementioning
confidence: 99%
“…21 Because an addiction counsellor is on site at the facility and other facility staff refer IDUs to addiction services, an evaluation was undertaken to examine factors associated with more rapid entry into a detoxification program among facility users. 33 Definition of this end point was based on linkage to a database maintained by Vancouver's 3 detoxification facilities, which offer medically monitored residential withdrawal services with on-site nursing and medical care. The study period considered each participant's recruitment date up until Mar.…”
Section: Referral For Addiction Treatment and Other Carementioning
confidence: 99%
“…Indeed, research has found that supervised injection services can play a role in facilitating uptake of addiction treatment services and promoting cessation from drug use. 12 Other studies have shown injection facilities have no adverse effects on drug use in the broader community, such as increasing rates of initiation into injecting among vulnerable populations. 13 Ultimately, these facilities appear to help advance the very goals that their opponents espouse.…”
mentioning
confidence: 99%
“…Theoretical possibilities of SIF expansion needs to be decided on by the local health authorities on the basis of scientific evidence supporting such expansion (17). Public awareness by the local health policy-makers and doctors regarding SIF will allow the community to be better educated about the benefits of these harm reduction programs and the role they play in reducing crime, drug dealing, public injection, and a host of other social maladies (9,(12)(13)(14)34,(46)(47)(48)(49)(50)(51). Community support is a fundamental part of sustaining the program and it will ultimately help in conceptualizing injection drug use as a health issue, rather than a moral one (11,16,53).…”
Section: Discussionmentioning
confidence: 99%